1998
DOI: 10.1002/14651858.cd000338
|View full text |Cite
|
Sign up to set email alerts
|

Condylocephalic nails versus extramedullary implants for extracapsular hip fractures

Abstract: Analysis 1.5. Comparison 1 Ender nails versus extramedullary fixation implants, Outcome 5 Cut-out of implant (odds ratio results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
0
16
0
4
Order By: Relevance
“…Although several systematic reviews of treatment options for extra-capsular fractures have been published in the Cochrane Library (e.g. [24,25]), a critical comprehensive review of the unstable fracture sub-group was missing. Systematic reviews are essential tools to provide evidence related to a particular field and are more objective than traditional narrative reviews [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although several systematic reviews of treatment options for extra-capsular fractures have been published in the Cochrane Library (e.g. [24,25]), a critical comprehensive review of the unstable fracture sub-group was missing. Systematic reviews are essential tools to provide evidence related to a particular field and are more objective than traditional narrative reviews [6].…”
Section: Introductionmentioning
confidence: 99%
“…8 In 90% of cases of extramedullary fixation implants, the average operative time were 120-150 minutes and mean blood loss was 400-600 ml. Mean operative time for intramedullary devices was 90-120 minutes with average blood loss of 3000400 ml.…”
Section: Discussionmentioning
confidence: 97%
“…Even the Cochrane library cannot give absolute answers on the best form of treatment [49,77,81,82]. This is largely a result of the paucity of studies and their poor quality in terms of outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane Database has concluded that the fixed nail plate has higher risks of implant breakage and fixation failure than the sliding hip screw for extracapsular hip fractures [49]. The evidence on other outcome measures is insufficient.…”
Section: Medoff Axial Compression Screwmentioning
confidence: 99%